Variations of aerosol and cloud vertical characteristics based on aircraft measurements in upstream of Shanghai during the 2020 China international import expo - Yu, Yang; Zhu, Qing; He, Qianshan; Gao, Yang; Zhou, Xu; Zhang, Rong; Zhang, Xiaotuo; Li, Hongyu; Wang, Weijie; Cheng, Tiantao (Frontiers in Environmental Science, 2022)
Vertical information about aerosols and clouds is vital to understanding aerosol transport, aerosol-cloud interactions, and pollution-weather-climate feedback so as to reduce uncertainties in estimating their climatic effects. The combination of sounding, lidar, aircraft, and satellite measurements is widely used to obtain the vertical information of aerosols and clouds. We used an aircraft measurement over southern Anhui, the upstream regions of Shanghai, on 1 November which conducted to ensure good air quality for the Third China International Import Expo to examine the vertical characteristics of aerosol and cloud microphysical properties and their variations before and after cloud seeding. Observations showed aerosols and clouds were vertically stratified. Most aerosols trapped within the boundary layer are small particles with sizes less than 0.12 µm. Aerosol number concentrations (Na) generally decreased with altitude in the cloudless atmosphere, with the largest particles occurring in 2500–3500 m due to dust transported from distant regions and high ambient humidity. Four separate cloud layers with unequal depths dominated by altostratus and nimbostratus appeared at different heights. The maximum cloud droplet concentration (Nc) and the minimum cloud droplet diameter (Dc) that appeared in the mid-level cloud (2246–2482 m) were 107.7 cm−3 and 4.03 μm, respectively, owing to the high proportion of hygroscopic particles. Hygroscopic particles played an important role in the growth of droplets and the activation of cloud condensation nuclei, especially under high ambient humidity. Cloud droplet size spectrum showed a unimodal distribution with a single peak at 5 µm in low- (970–1000 m) and mid-level clouds, but a trimodal distribution with peaks at 7 μm, 12 μm, and 17 μm in the mid-high- and high-level clouds, indicating the broadening of spectra with increasing altitude. An artificial seeding experiment was conducted in the high-level clouds. Big cloud droplets and ice crystals increased significantly after cloud seeding. Meanwhile, cloud particle populations showed less Nc, larger Dc, and a wider size spectrum. Our results suggest that the artificial precipitation experiment promoted rainfall to a certain extent and contributed to the removal of pollutants from upstream regions, which is beneficial to the air quality of Shanghai.